Analisis Kriminologi terhadap Bullying di Pesantren Al-Azhar Janapria, Lombok Tengah - Khafidah Nur Baiti; Taun (PT. Lembaga Penerbit Penelitian Nusantara, 2026)
The phenomenon of bullying in educational settings involving children and adolescents is increasingly worrying because it has serious physical and psychological impacts on victims. This study aims to analyze the criminological perspective on children as perpetrators of bullying and to identify the criminogenic factors that influence this behavior. The method used is normative legal research with a case study approach and a conceptual approach, utilizing secondary data from legal literature, journals, and bullying cases at the Al-Azhar Janapria Islamic Boarding School in Central Lombok. The results indicate that bullying behavior can be explained through strain theory, differential association theory, social control theory, and labeling theory. Bullying is influenced by faulty social learning processes, weak social control, and the application of negative labels. Criminogenic factors include the social environment, the individual, peers, and the family. Prevention efforts need to be carried out comprehensively through synergy between families, schools, and the community to create a safe and violence-free educational environment.